Inquiry and problem based pedagogy: Evidence from 10 field experiments - Rosangela Bando Grana; Emma Näslund-Hadley; Paul J. Gertler (Inter-American Development Bank (IDB), 2018)
We analyze evidence from 10 at-scale field experiments in four countries on the effect of inquiry- and problem-based pedagogy (IPP) on students' math and science test scores. IPP creates active problem solving opportunities in settings that derive meaning to the child. Students learn by collaboratively solving real life authentic problems, developing explanations, and communicating ideas. We find that IPP increased math test scores by 0.18 standard deviations and science test scores by 0.16 standard deviations after 7 months. Moreover, the results are robust across a wide set of geographic, socio-economic, and cultural, age/grade, and teacher background contexts.
Keywords: C93; I25; I38; O15; 330; Education; pedagogy; teacher effectiveness; mathematics; science; elementary education; inquiry-based learning; problem-based learning; early education